Gambaran Komitmen Pernikahan Pada Pasangan dengan Perbedaan Agama - Putera Redian, Mohamad Abrar; Sadida , Hanna Azfa; Khoirunnisa, Anindita; Alghifari, Fadhilah Afqa; Yuadi, Firzanatusalma Rafiza; Hendriani, Wiwin (Universitas Airlangga, 2024)
The aim of this research was to find out a picture of marital commitment in couples with differentreligions. Marital commitment in this research includes several aspects including: personal commitment,moral commitment, and restoration commitment. The research method used is a case study withparticipants as husband and wife couples who are still married with different religions, and with amarriage age of 1 year. Data mining was carried out using in-depth interviews, while technical dataanalysis used thematic analysis and was developed using a theory-driven method. Strengtheningresearch credibility uses source triangulation techniques by checking the data that has been obtained,namely the results of participant interviews, and also the theoretical basis used. Based on the results ofdata analysis, it can be found that the relationships between participants form individuals who havefeelings of dependence and create a bond of mutual belonging and promise to look after and trust eachother for a long time.